Miss Saigon special [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Interviews withe Filipino talents for Miss Saigon.
VHS.
Keywords: Filipino entertainers -- Philippines; ARTISTS; THEATER ARTS; HUMANITIES